Diffusion tensor imaging along the perivascular space may reveal potential pathological mechanisms underlying disease progression in primary open-angle glaucoma patients - Chen, Yilei; Xiao, Shuyu; Yan, Lvyu; Gong, Zhigang; Huang, Yanwen; Tan, Wenli; Yu, Ying (Frontiers in Neurology, 2025)
PurposeThis study investigates glymphatic system dysfunction in primary open-angle glaucoma (POAG) patients and explores its potential role in the progressive decline of visual function associated with the disease.MethodsThis prospective study compared 47 primary open-angle glaucoma (POAG) patients and 50 healthy controls (HCs) using multimodal MRI, including DTI, T1/T2-weighted imaging, and resting-state fMRI. Group differences in brain morphometry, spontaneous activity, perivascular space (PVS) volume, and DTI-ALPS index were analyzed, with regression and mediation models exploring their relationships. Ocular parameters (intraocular pressure, RNFL thickness, cup-to-disc ratio, visual field) were correlated with fMRI findings, particularly PVS and ALPS metrics.ResultsCompared to HCs, POAG patients exhibited significantly reduced cortical thickness, lower volume-wise Resting-state fMRI (Rs-fMRI) concordance (p < 0.001) and voxel-wise Rs-fMRI concordance (p < 0.05) in local intracranial regions, lower bilateral ALPS indices (p < 0.001), and higher volume fraction of the lateral ventricle body perivascular space (LVB-PVS) (p < 0.001). Linear regression models showed significant associations among left RNFL thickness, left ALPS index, LVB-PVS volume fraction, and cortical thickness of the left lingual gyrus (LING.L) (p < 0.05). Mediation analysis revealed that the left ALPS index partially mediated the associations between volume-wise Rs-fMRI concordance, cortical thickness of LING.L, and RNFL thickness. Furthermore, the ALPS index significantly mediated the relationship between LING.L cortical thickness and LVB-PVS volume fraction. However, no significant correlation was found between ALPS and the degree of visual field defect.ConclusionThe reduced ALPS index in POAG patients suggests impaired glymphatic clearance, which may impair metabolic clearance and contribute to RNFL damage, influencing disease progression.